Spectrographic analysis of speech of the hearing impaired children - Sowmya Narayan (Journal of All India Institute of Speech and Hearing, 1970)
"Great strides have been made in understanding the speech of the hearing impaired, but our knowledge in this area is far from complete" (Osberger andMcGarr1986). In the present study the speech of five severe/or profoundly congenital hearing impaired and five normal hearing Kannada speaking subjects has been analyzed spectrographically. Spectrographic analysis was done with the help of the computer and the following conclusions were drawn.